Пробіотичні бактерії в очищенні питної води від нітратів - Сапура, Олена Валеріївна; Гвоздяк, Петро Ілліч (My University, 2014)
У статті встановлено, що пробіотичні бактерії родів Bacillus, Streptococcus і Lactobacillus, які входять до складу лікарських препаратів, здійснюють процес денітрифікації питної води з понаднормованим вмістом нітратів. Очищення води здійснюється шляхом повільного фільтрування крізь зернисті (пісок, активоване вугілля) загрузки з іммобілізованими на них пробіотичними бактеріями. Концентрація нітратів у воді зменшується з 500...800 мг/дм3 до 2,5 мг/дм3 і нижче. We have investigated the purification of potable water from nitrate by means of the probiotic bacteria Bacillus subtilis, B. licheniformis as well as Lactobacillus acidophilus, L. bifidus, L. bulgaricus and Streptococcus thermophilus, which form part of corresponding medical preparations. It was shown that slow (0.1 m*h-l) filtration of water, with contents 300 ... 500 mg*l-l of nitrate, through the grain of sand and activated carbon, the chemical fiber under the pretext of carrier «VIYA» with immobilized probiotic bacteria on than, led to the reduction of nitrate concentration below 2,5 mg*l-l. Ethanol (0.1 ml to each 100 mg KN03) was added to treated water for support of microbial growth. The denitrification gas consisted of95 — 97% of N2, 0,1 ... 0.3% — C02, sometimes C2H4 (<1%), and (2 ... 3%) — H20 and did not contained H2, CH4, H2S. The biotests showed high quality and carelessness of obtained water
Keywords: пробіотичні бактерії; питна вода; очищення; нітрати; probiotic bacteria; potable water; purification; nitrate